On following pages: 7. Crabeater Seal (Lobodon carcinophaga): 8. Ross Seal (Ommatophoca rossi); 9. Bearded Seal (Erignathus barbatus); 10. Hooded Seal (Cystophora cristata). in Phocidae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
On following pages: 7. Crabeater Seal (Lobodon carcinophaga): 8. Ross Seal (Ommatophoca rossi); 9. Bearded Seal (Erignathus barbatus); 10. Hooded Seal (Cystophora cristata). Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Phocidae, pp. 120-183 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 173, DOI: 10.5281/zenodo.6607185